(untitled) (Academia Science Repository, 2023)
This article covers issues such as the formation of professional competence in future teachers and its content, the role and importance of base competencies in their preparation for professional activities, the formation of knowledge, skills and qualifications of students from Universal and specialized disciplines through interdisciplinary contacts, the mechanism of development of professional competence of students on the basis of pedagogical and technical.